Pengaruh Penerapan Etika Bisnis Kualitas Pelayanan dan Promosi terhadap Kepuasan Konsumen dalam Perspektif Islam di Rumah Makan Ilo Peta Kota Bima - Nisa, Rahmatun; Parakasi, H. Idris; Sofyan, A. Syatir (ARZUSIN, 2023)
This study aims to determine the effect of the application of business ethics, service quality and promotion on consumer satisfaction in an Islamic perspective at the Ilo Peta Kota Bima restaurant. Business ethics influences customer satisfaction in an Islamic perspective seen from services that have a good level of ethics, service quality affects consumers who provide services according to Islamic law, promotions affect consumer satisfaction seen from the absence of lies in each advertisement so that people can be interested and easily known by the general public. The purpose of this study was to see how far the influence of business ethics, service quality and promotion on customer satisfaction at the Ilo Peta restaurant, Kota Bima. In this study, a quantitative approach was used, with a sample of 257 respondents and the analytical technique used in the study used multiple linear analysis, data that met the requirements for analysis were processed using the SPPS program. From the results of statistical testing the results of this study regarding the application of business ethics, service quality and promotion have a positive, simultaneous and significant effect on customer satisfaction in an Islamic perspective.